Some Estimation Approaches of Intensities for a Two Stage Open Queueing Network - Pathare, Suresh B; Gedam, Vinayak K (Statistics, Optimization & Information Computing, 2014)
In this paper we propose a consistent and asymptotically normal estimator (CAN) for intensity parameters for a queueing network with distribution-free inter-arrival and service times. Using this estimator and its estimated variance, some asymptotic confidence interval of intensities are constructed. Exact- t, Bootstrap-t, Variance-stabilized bootstrap-t, Standard bootstrap, Bayesian bootstrap, Percentile bootstrap and Bias-corrected and accelerated bootstrap are also applied to develop the confidence intervals of intensities. A comparative analysis is conducted to demonstrate performances of the confidence intervals of intensities for a queueing network with short run.